Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) terhadap Keterampilan Menulis Teks Eksplanasi pada Siswa Kelas V SDN 17 Pontianak Kota - fera fera; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2024)
This research aims to test the influence of the Think Talk Write (TTW) type cooperative model on explanatory text writing skills in class V students at SDN 17 Pontianak Kota in particular. The research method used is an experimental method in the form of a quasi experimental design, with a nonequivalent control group design. The population in this study were all students in class V of Pontianak City 17th State Elementary School. The sample was determined using a purposive sampling technique and obtained a sample of class VA totaling 26 students as the control class and class VB totaling 27 students as the experimental class. Data collection techniques use measurement techniques. The data collection tool used was a test of explanatory text writing skills. Based on data analysis, the average learning outcome for the experimental class was 80.46 and the average learning outcome for the control class was 76.57. The results of the t test obtained tcount 2.44 and ttable α = 5% and dk = 26 + 27 – 2 = 51 is 2.000, then Ha is accepted, so it can be concluded that there is an influence of the Think Talk Write (TTW) type cooperative model on explanatory text writing skills in class V students at SDN 17 Pontianak Kota. From the effect size (ES), an ES of 0.34 (medium criteria) was obtained. This means that the Think Talk Write (TTW) type cooperative model has a moderate influence on the explanatory text writing skills of fifth grade students at SDN 17 Pontianak City.